Pembangunan Sistem Analisis Kecenderungan Kerjaya Pelajar - Muhammad Amirnurhakim Mohd Nazri; Mohd Zaki Mohd Salikon (Applied Information Technology And Computer Science, 2021)
Abstract: SMK Seremban Jaya 2 Student Career Tendency Analysis System is a system developed with the function to identify a student’s career inclination through their personalities. Currently, students at SMK Seremban Jaya 2 have to answer career questions using paper forms. Then the counseling teacher has to re-collect the papers answered by the students and calculate the marks manually of each student to know their results. This poses problems especially during revision, storage, and calculation of marks which are prone to negligence. Furthermore, this method can lead to incorrect entry of marks and information. Therefore, a system for analyzing career tendencies was developed online. The system has a system and database interface and is supported by online operations to make its operation more systematic and save time in terms of usage. It also makes it easier for students to answer questions online and also makes it easier for counseling teachers as the system has an automatic calculation function for the calculation of results. The system was developed using a web-based decision support system approach. The Prototype Model is used as a system development guide. Sublime software is used as editing software for coding, and xampp as a database as well as a system server. There are 7 functions of the system, namely Entry Registration Module, Career Info Module, Test Module, Comment Module, Report Module, Examination History Module, and Appreciation Module. Finally, it is expected that the career analysis system of SMK Seremban Jaya 2 will be able to benefit the counseling unit as well as students at SMK Seremban Jaya 2 because this system is able to overcome all the problems faced.